1997
DOI: 10.2134/jpa1997.0572
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term P and K Applications: II. Effect on Corn and Soybean Yields and Plant P and K Concentrations

Abstract: Increasing emphasis on environmentally sound nutrient management requires an improved understanding of fertilizer P and K needs for profitable crop production. A 20‐yr study was conducted on two glacial till soils to determine: (i) the effect of various P and K rates on corn (Zea mays L.) and soybean (Glycine max (L.) Merr.] yields and profitability during a 12‐yr application phase and an 8‐yr residual phase, and (ii) whether triennial applications of P and K produce crop yields equal to those from annual appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 9 publications
3
26
0
Order By: Relevance
“…Larger yields were associated with improvement in K uptake, reductions in K seed and KHI, and a substantial increment in K stover , leading to a reduction in KIE over time. Increases in K stover were also reported by others (Heckman and Kamprath, 1995; Randall et al, 1997; Clover and Mallarino, 2013).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Larger yields were associated with improvement in K uptake, reductions in K seed and KHI, and a substantial increment in K stover , leading to a reduction in KIE over time. Increases in K stover were also reported by others (Heckman and Kamprath, 1995; Randall et al, 1997; Clover and Mallarino, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…In this review, K stover was larger in Eras II and III than in Era I, which can be related to the increase in K fertilization since 1960 (USDA‐ERS, 2016). Several authors have reported increases in K stover with K fertilization and without yield response in corn and soybean (Heckman and Kamprath, 1995; Randall et al, 1997; Clover and Mallarino, 2013). Luxury nutrient uptake occurs when uptake is above the crop requirement for a target yield level.…”
Section: Discussionmentioning
confidence: 99%
“…Many leguminous crops are sensitive to Cl − toxicity, including soybean 120,131 and alfalfa 159,160,198 , and Cl − can reduce soil N availability by inhibiting nitrification in soils 195,196,199,200 (see also supplementary references [53][54][55] for the online version of the paper) and by acting as a competitive anion that suppresses plant uptake of NO 3 − 147,201,202 (see also supplementary references [38] and [56][57][58][59] for the online version of the paper). A further difficulty arises from the mobility of Cl − in soils, which intensifies profile leaching of Ca 2 + as a counterion [203][204][205] .…”
Section: ----------------------------------------Kg Ha − 1 ----------mentioning
confidence: 99%
“…In these developing countries, the challenge is the optimization of the use of small amounts of fertilizer N affordable by resource-poor farmers (Atchou 1988;Pieri 1989;Saragoni et al 1991), unlike industrialized councomplex. Studies using drain lines and lysimeters to collect drainage water have been conducted to address fertilizer N use efficiency, nitrate leaching, and water quality issues (Magdoff et al 1984;Roth and Fox 1990;Angle et al 1996;Randall et al 1997;Sogbedji et al 2000;Fofana et al 2004), but efficient N management remains a challenge due to the complexity associated with N dynamics in the soil-plant-atmosphere system (Kladivko et al 1991;van Es et al 1991). Addiscott et al (1991) concluded that, as many physical, chemical and biological processes affecting soil N can happen practically at once, any attempt at a simultaneous description of its dynamics requires an explicit, computer-based, model.…”
Section: Introductionmentioning
confidence: 99%